Neonatal sepsis, clinical manifestation, diagnosis and treatment - Marusyk, Uliana Ivanivna; Vlasova, Olena Vasylivna; Hrytsiuk, Maryana Ivanivna; Bebykh, Valentyna Volodymyrivna (Journal of Education, Health and Sport, 2019)
Sepsis is a severe illness during the neonatal period. Despite significant advances in the care of newborn infants, sepsis remains a leading cause of neonatal morbidity and mortality. The overall incidence of neonatal sepsis ranges from 1 to 5 cases per 1,000 births and case fatality rates (CFRs) range from 2 % to 60 %. Both rates depend on multiple factors, such as pathogen distribution, gestational age, Streptococcus agalactiae (group B Streptococcus, GBS) carriage rates and prevalence of other common specific pathogens. Most types of microorganisms can cause sepsis, including bacteria, fungi, viruses and parasites, such as those that cause malaria. Bacteria such as Streptococcus pneumoniae, Haemophilus influenzae, Staphylococcus aureus, Escherichia coli, Salmonella and Neisseria meningitidis are the most common etiological pathogens. Manifestations of sepsis and septic shock can be the fatal frequent pathway of infections with seasonal influenza viruses, dengue viruses and highly transmissible pathogens of public health concern such as avian and swine influenza viruses, severe acute respiratory syndrome coronavirus, Middle East respiratory syndrome coronavirus and most recently, Ebola and yellow fever viruses. It is descriptive, non-experimental study. The aim of it is to specify the etiologic factors, clinical manifestation, diagnostic criteria and treatment of sepsis. Based on the results of the study conclusion is that the use of non-culture based diagnostics and sepsis scores to predict and diagnose septic neonates are areas of active investigation. The next frontier for antibiotic stewardship in the neonatal intensive care unit must be development of strategies to decrease antibiotic use and minimise adverse effects by a thorough study of duration of therapy.